318 A MOUSE MODEL OF HEREDITARY HEMOCHROMATOSIS EXHIBITS INCREASED INSULIN SENSITIVITY AND RESISTANCE TO DIET-INDUCED OBESITY, WHILE WILD-TYPE MICE FED EXCESS IRON ARE INSULIN RESISTANT. (1st January 2006) - Jouihan, H.; Cooksey, R.; Jones, D.; Gabrielsen, S.; McClain, D.
Abstract : Hereditary hemochromatosis (HH) is a common genetic disorder characterized by iron overload and diabetes, although the mechanism underlying the diabetes remains controversial. We have previously demonstrated that mice with knockout of the human gene most commonly mutated in HH ( Hfe - / - ) exhibit decreased beta cell mass and insulin secretion secondary to beta cell apoptosis and a desensitization of glucose stimulated insulin secretion. In the Hfe - / - mice and HH humans the decreased insulin secretion is partially compensated by increased insulin sensitivity. In contrast, iron overload has also been reported in insulin-resistant humans with the metabolic syndrome and/or type 2 diabetes. To study the mechanisms underlying these different phenotypes, we have created a model of mice that are fed excess dietary carbonyl iron in combination with a high-fat diet and compared them to the HH ( Hfe - / - ) mice also fed a high-fat diet. On high fat, the Hfe - / - mice are resistant to diet-induced obesity ( Hfe - / -, 31.9 g, wild type 36.8 g, p < .02). When studied by intraperitoneal glucose tolerance testing (IPGTT), the Hfe-/-mice also exhibit decreased glucose excursions (19% decrease in the area under the glucose curve, p < .01) with decreased insulin levels (38% decrease at 30 min, p < .05). By contrast, compared to mice on a high-fat diet with normal iron, the iron-fed mice weigh more (38.4 vs 35.6 g, p < .05) and have a 45% increase in glucose excursion during IPGTT (p < .002) despite a 50% increase in serum insulin (p = .02). Thus, in a mouse model, excess dietary iron exacerbates aspects of the metabolic syndrome and leads to a phenotype similar to type 2 diabetes, while iron overload resulting from hereditary hemochromatosis results in protection from these markers of the metabolic syndrome and an insulin-deficient phenotype. The protection afforded the Hfe-/- model can be accounted for by thermogenesis resulting from mitochondrial damage, and the difference in the phenotypes likely results from the different tisssue distributions of iron in the two models. NIH DK 59512.